Glossário escolar : uma construção do aluno - Silva, Fablinne Marani Pereira (2015)
This study aims to apply an education intervention proposal which took students from the ninth grade of fundamental education from a public school to elaborate glossaries of terms from different disciplines and to spell lexical items studied. The methodology adopted for this intervention was based on research-action and the activity steps were detailed with the objective of describing all the construction stages of the individual educational glossary from the interaction with the group. The literature review brings considerations about the lexicon sciences, emphasizing the teaching of the lexicon for vocabulary enrichment. Contributed to the revision: Barbosa (1981) (1986) (1990) and (2009), Biderman (2001), Dias (2004), Galisson (1979), Garcia (2006), Matoré (1953), Picoche (1977), Vilela (1995), among others. Being the comprehension of the meanings of the words and terms the first step to direct the construction of other knowledge, the use of printed and online dictionaries as a source of research is paramount. With the analysis of glossaries, we understand that the activities that make the students research, both to record dictionary definitions as to build their own definitions, make the teachers rethink their teaching practice. Like any terminology research, we believe that the result led us to interesting considerations about our role as teacher and more: about the importance of lexicon teaching in fundamental education.